What is "marked" in visual marking? Evidence for effects of configuration in preview search. - Kunar, M; Humphreys, G; Smith, K; Hulleman, J (2003)
Visual search for a conjunction target is facilitated when distractor sets are segmented over time: the preview benefit Watson and Humphreys (1997) suggested that this benefit involved inhibition of old items (visual marking, VM). We investigated whether the preview benefit is sensitive to the configuration of the old distractors. Old distractors changed their location prior to the occurrence of the new items, while also either changing or maintaining their configuration. Configuration changes disrupted search. The results are consistent with object-based VM, which is sensitive to the configuration of old stimuli.